Diabetic peripheral neuropathy: pain management - Antoine-Frank, Chrystal D.; Ellis, Kaydeonne T.; Antoine, Malcolm R.; Annan, Pars Daniel; Seyni-Boureima, Rimanatou (International Journal of Advances in Medicine, 2021)
As diabetes mellitus continues to be a global health issue, more and more cases of macro-vascular and micro-vascular complications are being commonly observed amongst this category of patients. One micro-vascular complication often seen in diabetic patients is diabetic neuropathy as at least 50% of diabetic patients will experience some form of neuropathy following a diagnosis of diabetes for about 25 years. Even though diabetic patients are at risk for developing various types of neuropathies, polyneuropathies are most commonly observed and develop mainly develop due to hyperglycaemia, dyslipidemia and abnormal insulin signaling. Polyneuropathies are commonly accompanied by bilateral sensory loss in the distal limbs. Varying degrees of pain are also observed with this complication and pain management may serve to be very complicated. Therefore, this review discusses neuropathy focusing specifically on the effective management of the pain that commonly accompanies this diabetic complication.